2011
DOI: 10.1115/1.4003115
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Specific Absorption Rate and Heat Transfer in the Human Body Exposed to Leakage Electromagnetic Field at 915 MHz and 2450 MHz

Abstract: In recent years, society has increased utilization of electromagnetic radiation in various applications. This radiation interacts with the human body and may lead to detrimental effects on human health. However, the resulting thermophysiologic response of the human body is not well understood. In order to gain insight into the phenomena occurring within the human body with temperature distribution induced by electromagnetic field, a detailed knowledge of absorbed power distribution is necessary. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…10,246 Microwave ablation is another application of microwaves which could be used for the treatment of liver cancer. [247][248][249][250] Microwave energy is emitted by the Microwave Coaxial Antenna (MCA) which generates heat in the local cancerous tissue without affecting the surrounding tissue. 247 Wessapan et al 248 carried out numerical studies on the temperature distribution and specific absorption rate of microwaves in human body which was exposed to different frequencies.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,246 Microwave ablation is another application of microwaves which could be used for the treatment of liver cancer. [247][248][249][250] Microwave energy is emitted by the Microwave Coaxial Antenna (MCA) which generates heat in the local cancerous tissue without affecting the surrounding tissue. 247 Wessapan et al 248 carried out numerical studies on the temperature distribution and specific absorption rate of microwaves in human body which was exposed to different frequencies.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…[247][248][249][250] Microwave energy is emitted by the Microwave Coaxial Antenna (MCA) which generates heat in the local cancerous tissue without affecting the surrounding tissue. 247 Wessapan et al 248 carried out numerical studies on the temperature distribution and specific absorption rate of microwaves in human body which was exposed to different frequencies. It was found that at 2.45 GHz, the maximum temperature was found at the skin whereas at 915 MHz, the maximum temperature was found at the fat.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Our research group has numerically investigated the temperature increase in human tissue subjected to EM fields in regard to many problems [37][38][39][40][41][42][43][44][45]. Wessapan et al [38,39] utilized a 2D finite-element method (FEM) to determine the specific absorption rate (SAR) and temperature increase in the human body exposed to leaking EM waves.…”
Section: Introductionmentioning
confidence: 99%
“…Wessapan et al [38,39] utilized a 2D finite-element method (FEM) to determine the specific absorption rate (SAR) and temperature increase in the human body exposed to leaking EM waves. Wessapan et al [40,41] developed a 3D model of the human head in order to investigate the SAR and temperature distributions in the human head during exposure to cellphone radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the expanded utilization of electromagnetic (EM) wave in various fields, one of the most challenging problems is EM interference and pollution, which could cause disturbance on the devices and systems and even threaten the health of animals and human beings [1][2][3][4] . In response to the need for protecting human beings from EM wave irradiation and preventing the military equipment from being detected by radar waves, the development of effective EM wave absorption materials have attracted a world of attention.…”
Section: Introductionmentioning
confidence: 99%